Performance Investigation of a GridTie Pv System Under Iraqi Solar Circumstances Based on MATLAB/Simulation (Eurasian Journal of Engineering and Technology, 2022)
Due to the longer days and yearly sunlight hours, solar photovoltaic (PV) power systems are one of Iraq's greatest alternative energy sources. The on PV power system is described in this study as one that runs in parallel with the local grid (only during daylight hours) to either supply household appliances or back-feed the grid when the PV system's output power exceeds household requirements. The key issue of creating the suggested system is an ability toward integrate energy converters with the relevant control mechanism to get the greatest performance. For obtaining optimum power and controlling AC voltage, a current controller and a voltage controller are proposed. This study aims to show how on-grid PV systems function under real-world daily irradiance in Baghdad in July. According to the simulation findings, the PV array's percentage power yield is 95 per cent when the MPPT algorithm is used. Furthermore, the load current waveform is sinusoidal, having a low total harmonic distortion (THD), 0.49 per cent for current and 0.58 per cent for voltage